2011
DOI: 10.1007/s00264-011-1342-3
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term results after total clavicle resection in cases of osteitis: a consecutive case series of five patients

Abstract: Purpose Claviculectomy is a rare and poorly described event in the surgical therapy of diseases of the clavicle. We present a case series and functional results of patients who underwent total claviculectomy. Methods From 1995 to 2006 a total of 26 patients diagnosed with osteitis of the clavicle underwent surgery in our unit. Of these, five patients (all female) needed a total resection of the clavicle in order to ensure permanent healing from infection. The data collection was prospective. The data gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several studies in the literature reported good results after TCR. Oheim [64] et al, reported 5 patients treated with total clavicle resection for osteitis. The average Constant score showed a significant improvement, from 82 to 95, after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature reported good results after TCR. Oheim [64] et al, reported 5 patients treated with total clavicle resection for osteitis. The average Constant score showed a significant improvement, from 82 to 95, after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory analyses are widely known to be a helpful tool in infection diagnosis, CRP being more sensitive than a high leucocytes count, but these analyses can produce negative results despite the presence of a severe infection [9, 27]. As stated previously, the clinical suspicion of an infection, or empyema, must be an individual composition of clinical signs, laboratory analyses and imaging [25]. The diagnosis should be confirmed by histological examination and/or verifiably organism growth.…”
Section: Discussionmentioning
confidence: 99%
“… 91 Total claviculectomy has been described after multiple failed procedures. 94 Given the proximity to vascular structures, the procedures are best carried out in conjunction with thoracic surgeons. 74 …”
Section: Non-traumatic Disorders Of the Scjmentioning
confidence: 99%